PENGARUH PEMBELAJARAN SCAFOLDING TERHADAP PEMAHAMAN KONSEP INTEGRAL MAHASISWA - Satrio Wicaksono Sudarman; Nego Linuhung (UNIVERSITAS MUHAMMADIYAH METRO, 2017)
The research was conducted to find out the influence of learning model of scaffolding to understanding consept of integral. The design of this research is quasi experiment consisting of 1 experiment class and 1 control class. The purpose of this research is to examine and know the difference understanding concept of integral, students who obtained learning model of scaffolding and students who received conventional learning. This research was conducted at Muhammadiyah University of Metro. The population is all students of mathematics semester 2 Universitas Muhammadiyah Metro. Two classes are drawn into a sample, 1 class as a control class and 1 other class is given learning model of scaffolding. Based on the results of research that has been done can be concluded that there is a difference understanding integral concept students who obtain learning model of scaffolding and students who obtain conventional learning.